Increasing the Utilization of Bamboo for Rainwater Capture Networks in Batu Jaran Hall, Batulayar Village - Yasa, I Wayan; Hasyim, Hasyim; Karyawan, I Dewa Made Alit; Jayanegara, I Dewa Gede; Saidah, Humairo; Rohani, Rohani; Agastya, Dewandha Mas (Pascasarjana Universitas Mataram, 2024)
The problem of clean water for people in the highlands always arises every dry season. Getting clean water every day requires a lot of effort to find a water source that is very far away. Some people even have to spend additional money to get clean water. This is also the case with people in Batulayar sub-district who live in the highlands, especially in the mountains. Surface water sources are not available so that it becomes a routine problem every year. In overcoming this problem, some people make rainwater reservoirs either in groups or individually. The reservoir is made with several materials in the form of a reservoir by making a hole in the ground surface covered with plastic or tarpaulin and a reservoir made of brick/brick masonry. The method of capturing water is directly from the ground surface by making a channel and there is by making a reservoir from local materials in the form of bamboo which then the captured water is channeled into the reservoir. The use of local materials in the form of bamboo is very potential to be used because in the Batulayar area, especially in the mountains, the availability of bamboo is very abundant. Bamboo with an age of 3 years already has quite high strength both for water flow materials and as construction materials. The weakness that is still faced by the community in utilizing bamboo is the connection method which is still very simple, so that when it rains with high intensity the connection comes loose. In using bamboo as a rainwater catchment network, it is very important to socialize the right connection model to be used in capturing rainwater.